Efektivitas Prenatal Yoga Untuk Mengurangi Nyeri Punggung Pada Ibu Hamil Trimester III - Talita Putri Idasa Richa Nur Pratama; Nur Azizah Indriastuti (Lembaga Pengembangan Kinerja Dosen, 2023)
Pregnancy is a physiological process that occurs due to the process of growth and development of a fetus. During the development of pregnancy there will be physical and mental changes. One of the physical changes that occur during pregnancy is pregnant women experience complaints of back pain, especially in III trimester. Efforts to reduce back pain in third trimester pregnant women are using prenatal yoga. This case study purpose to determine the effect of applying prenatal yoga on back pain in III trimester pregnant women. The method in this study is a case study on clients of III trimester pregnant women. Patients were measured with OPQRSUV and used NRS instrument to determine pain scale before and after prenatal yoga intervention. The intervention was carried out for 3 days with 15-30 minutes every session. The results of this case study showed that prenatal yoga intervention in pregnant women can reduce the level of back pain from scale 4 to scale 2 within 3 days intervention. The implication of this case study is prenatal yoga which consists of 6 effective movements to help reduce the scale of pain in III trimester pregnant women because it can relax the body of pregnant women.